Trimeric Autotransporter Adhesin-Dependent Adherence of Bartonella henselae, Bartonella quintana, and Yersinia enterocolitica to Matrix Components and Endothelial Cells under Static and Dynamic Flow Conditions - Müller, Niklas F. (American Society for Microbiology, 2011)
Trimeric autotransporter adhesins (TAAs) are important virulence factors of Gram-negative bacteria responsible for adherence to extracellular matrix (ECM) and host cells. Here, we analyzed three different TAAs (Bartonella adhesin A [BadA] of Bartonella henselae, variably expressed outer membrane proteins [Vomps] of Bartonella quintana, and Yersinia adhesin A [YadA] of Yersinia enterocolitica) for mediating bacterial adherence to ECM and endothelial cells. Using static (cell culture vials) and dynamic (capillary flow chambers) experimental settings, adherence of wild-type bacteria and of the respective TAA-negative strains was analyzed. Under static conditions, ECM adherence of B. henselae, B. quintana, and Y. enterocolitica was strongly dependent on the expression of their particular TAAs. YadA of Y. enterocolitica did not mediate bacterial binding to plasma or cellular fibronectin under either static or dynamic conditions. TAA-dependent host cell adherence appeared more significant under dynamic conditions although the total number of bound bacteria was diminished compared to the number under static conditions. Dynamic models expand the methodology to perform bacterial adherence experiments under more realistic, bloodstream-like conditions and allow dissection of the biological role of TAAs in ECM and host cell adherence under static and dynamic conditions.